Epidemiology and Characteristics of Plastic Surgery Cases in Simpang Lima Gumul General Hospital, Kediri Regency During Covid-19 Pandemic - Wirawan, Nathania Carolina; Herihadi, Eko (Lingkar Studi Bedah Plastik Foundation, 2021)
Backgrounds: Chinese Government found the first case of coronavirus disease 2019 (COVID-19) in Wuhan, China, in December 2019. The pandemic impacts the number of visits to plastic surgery clinics in many countries such as Italy and the United States following surgical limitations. This study was aimed to determine the impact of the pandemic on the field of Reconstructive and Aesthetic Plastic Surgery in Indonesia, particularly in Kediri Regency, East Java.Methods: The study design was an analytical cross-sectional study, using data obtained from the medical records of plastic surgery patients at SLG General Hospital in Kediri Regency. The data analysis included descriptive analysis and dummy regression analysis.Results: This study included a total of 29 observations, 14 before the pandemic era and 15 during the pandemic, with a total of 460 individuals from various diagnostic categories. Based on the findings, the number of patients diagnosed with Congenital Disorders, Skin, and Soft Tissue, and Aesthetic Surgery dropped by 7%, 2%, and 6%, respectively. Meanwhile, there was an increased number of patients with Maxillofacial, Burn and Wound Care, and Hand and Microsurgery by 5%, 4%, and 1%, respectively. Conclusions: The average number of patient visits for the Skin and Soft Tissue, Burn and Wound Care, and Hand and Microsurgery categories did not vary much during this pandemic.